Physicochemical and Morphological Characterisation of the Native and Alkaline Pre-treated Fibre Pressed Oil Palm Frond for Fermentable Sugars Production - Fatin Syazwana, Hashim; Hafizuddin, Wan Yussof; Mior Ahmad Khushairi, Mohd Zahari; Roshanida, A. Rahman; Rosli, Md Illias (The Italian Association of Chemical Engineering, 2017)
Lignocellulosic biomass (LCB) is the most abundant renewable biomass that gives high potential source for the production of value added products. LCB is mainly composed of cellulose, hemicellulose and lignin. During pretreatment process, cellulosic biomass structure will be altered and delignification occur which make cellulose more accessible to the subsequent process of converting it into simple sugars. In this study, fibre pressed oil palm frond (FPOPF) was introduced as a raw material in order to maximise the utilisation of oil palm waste. This study was conducted to analyse and compare the physical, chemical and morphological characteristics of FPOPF before (native) and after alkaline pretreatment (pre-treated). The FPOPF was subjected to an alkaline pretreatment at 4.42 % w/v of sodium hydroxide solution which operated at 100 °C for an hour (Sukri and Rahman, 2014). From the study, it was found that characterisation of native FPOPF produced 40.7 % glucan, 26.1 % xylan, 4.5 % extractives, 26.2 % lignin and 1.8 % ash. Pre-treated FPOPF gave 61.4 % glucan, 20.4 % xylan, 0.3 % extractives, 13.3 % lignin and 1.3 % ash. The FPOPF samples were characterised using X-ray Diffraction spectrometry (XRD), Fourier Transform Infrared spectroscopy (FTIR), and Scanning Electron Microscopy (SEM) to evaluate the properties and structural changes of FPOPF between native and pre-treated FPOPF. This information is useful in order to understand the properties and structural changes for native and pre-treated FPOPF.